Dystopia, Alternate History and the Posthuman in Bioshock - Lars Schmeink (Current Objectives of Postgraduate American Studies)
In dystopian visions articulated at the beginning of the twenty-first century, one can observe a tendency to approach biotechnology as implicating the threat of posthumanity. Different media explore such perspectives on the future and it is the goal of my paper to analyze the specific perspective that informs the medium of video games. I propose to read the game Bioshock “from a dialectic of video games studies and literary studies, focusing on its uses of simulation and agency, its appropriation of alternate history and dystopia, and its treatment of a posthuman society.